1853 Ky. Acts 186, ch. 1020, §§ 1, 2 - (:unkn) unknown (General Publisher, 1854)
Prohibited the concealed carry of any deadly weapons. Violators fined not less than fifty nor more than one hundred dollars on first conviction. Subsequent convictions fined not less than one hundred nor more than five hundred dollars.
--
Keywords: CARRY - CONCEALED